Classroom Management Practices of Secondary School Teachers in Wah Cantt, Rawalpindi, Punjab: A Survey Study - Dr. Muhammad Naqeeb ul Khalil Shaheen; Hajira Naqeeb; Saba Sadiq (Journal for Social Science Archives, 2025)
Managing classrooms effectively is a main factor in determining the success of teaching and learning. However, teachers are rarely able to establish disciplined and productive learning environments. This research explored secondary school teachers’ classroom management strategies in Wah Cantt, Rawalpindi, Punjab. The teacher management practices focused on were organizing learning materials, surprise visits, notebook checking, character building, polite behavior, parent-teacher meetings, student recognition, eye contact, collaboration, mutual respect, conflict resolution, cooperative learning, problem-solving, rule establishment, positive reinforcement, and understanding of consequences. A descriptive cross-sectional survey design was used. The population consisted of secondary school teachers of government sector schools in Wah Cantt, Rawalpindi, Punjab. Through simple random sampling, 320 teachers were picked as a sample. A 16-item, five-point Likert scale questionnaire was conceptualized and validated by educational experts. Reliability was assured through pilot testing. Data were analyzed using frequency, percentage, and mean scores. According to the findings, a great majority of teachers manage the learning materials; most teachers carry out surprise visits; many teachers do random notebook checking; teachers mainly concentrate on character development; the majority of teachers behave politely; the majority of teachers meet parents; teachers learn the names of students; teachers mainly use eye contact; a very high percentage of teachers start with collaborative activities; a very high percentage of teachers promote mutual respect; teachers mostly support conflict resolution; teachers mostly teach cooperative learning; more than half of the teachers use problem-solving; a great majority of the teachers engage students in rule-making; more than half of the teachers give positive reinforcement; and most of the teachers make aware of consequences. The study found secondary school teachers in Wah Cantt to be moderately to highly engaged in classroom management practices. Collaborative activities and mutual respect were the strongest areas of these teachers. The recommendations included giving proper training, involving students in rule-making, preparing engaging activities, developing caring behavior, and focusing on effective lesson planning.